A Three-Dimensional Co-Culture Model for Rheumatoid Arthritis Pannus Tissue - Lin, Jietao; Sun, Antonia RuJia; Li, Jian; Yuan, Tianying; Cheng, Wenxiang; Ke, Liqing; Chen, Jianhai; Sun, Wei; Mi, Shengli; Zhang, Peng (Frontiers in Bioengineering and Biotechnology, 2021)
Three-dimensional (3D) co-culture models have closer physiological cell composition and behavior than traditional 2D culture. They exhibit pharmacological effects like in vivo responses, and therefore serve as a high-throughput drug screening model to evaluate drug efficacy and safety in vitro. In this study, we created a 3D co-culture environment to mimic pathological characteristics of rheumatoid arthritis (RA) pannus tissue. 3D scaffold was constructed by bioprinting technology with synovial fibroblasts (MH7A), vascular endothelial cells (EA.hy 926) and gelatin/alginate hydrogels. Cell viability was observed during seven-day culture and the proliferation rate of co-culture cells showed a stable increase stage. Cell-cell interactions were evaluated in the 3D printed scaffold and we found that spheroid size increased with time. TNF-α stimulated MH7A and EA.hy 926 in 3D pannus model showed higher vascular endothelial growth factor (VEGF) and angiopoietin (ANG) protein expression over time. For drug validation, methotrexate was used to examine inhibition effects of angiogenesis in 3D pannus co-culture model. In conclusion, this 3D co-culture pannus model with biological characteristics may help the development of anti-RA drug research.